Estimasi Parameter Model Fungsi Gaji Berdasarkan Masa Kerja Menggunakan Algoritma Levenberg-Marquardt pada Program Matlab - Atika Ratna Dewi; Sulistiyasni Sulistiyasni; Dewi Erla Mahmudah; Riana Safitri (LPPM STMIK Widya Utama, 2018)
The calculation of pension funding programneeds an assumption which can be used to predict theamount of salary when somebody is retired. This iscommonly called salary function. A salary function wasinfluenced by some factors such as inflation and merit. Thisstudy discussed the declining of salary function model basedon exponential function. The salary function model wasbased on years of service (service-based model). This modelhad been estimated using Levenberg Marquardt method onMATLAB program. After that, the model had been used tocalculate the amount of salary on pension funding program.